Design a Wideband Low-Noise Amplifier for Wireless Communication using 0.35-µm CMOS Technology - Mohd Hafiz Abu (Universiti Malaysia Perlis, 2008)
Low Noise Amplifier (LNA) is one of the receiver front end component. Place near antenna, this part used to minimize the noise figure of the amplifier while providing enough gain with sufficient linearity to overcome the noise of subsequent stage. It is commonly used to amplify signal that are to weak for direct processing for example in radio and cable receiver. For this project, some specification to design Low Noise Amplifier are picked from Digital Enhanced Cordless Telecommunication (DECT) specification. During designing the amplifier, the characteristic of the low- noise amplifier has been study. Thus, the core amplifier of the low noise amplifier consist of simple common source transconductance structure for the first stage and the second stage used common source amplifier with active shunt- shunt feedback. The advantage by using the feedback structure is the amplifier reduce effect of noise that occur and reduce non-linear distortion as the output proportional with the input. The design of the Low Noise Amplifier used Mentor Graphic software by using 0.35tsmc (Taiwan Semiconductor Manufacturing Company) for design and simulation process. At the end of the process, layout of the Low Noise Amplifier has been produce and ready to be fabricated at clean room.